Volume 3: Heat Transfer; Electric Power; Industrial and Cogeneration 2001
DOI: 10.1115/2001-gt-0151
|View full text |Cite
|
Sign up to set email alerts
|

Mist/Steam Cooling by a Row of Impinging Jets

Abstract: Closed loop steam has been chosen for cooling airfoils in heavy frame Advanced Turbine Systems (ATS) to improve efficiency. Enhanced cooling by the use of mist is considered to have potential to augment cooling by internal steam alone. Water droplets generally less than 10μm are added to 1.3 bar steam and injected through a row of four discrete round jets onto a heated surface. The Reynolds number is varied from 7500 to 22500 and the heat flux varied from 3.3 to 13.4 kW/m2. The mist increases the heat transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 0 publications
0
14
1
Order By: Relevance
“…The overall cooling enhancement ranged from 40% to 300% with the maximum local cooling enhancement being over 800%, which occurred at about 45 o downstream of the inlet of the test section. Li et al [13] reported results of mist/steam cooling with a slot jet on a heated flat surface. Their results showed a 200% cooling enhancement near the stagnation point by adding 1.5% mist (in mass) to the steam flow.…”
Section: Gt2005-69100mentioning
confidence: 99%
See 1 more Smart Citation
“…The overall cooling enhancement ranged from 40% to 300% with the maximum local cooling enhancement being over 800%, which occurred at about 45 o downstream of the inlet of the test section. Li et al [13] reported results of mist/steam cooling with a slot jet on a heated flat surface. Their results showed a 200% cooling enhancement near the stagnation point by adding 1.5% mist (in mass) to the steam flow.…”
Section: Gt2005-69100mentioning
confidence: 99%
“…Models of collisions and coalescences will also be developed and incorporated into the future studies. Li et al modeled the mist cooling [22] using the experimental data from [13] and reported the major contribution for mist cooling enhancement was from the direct contact between droplets and the wall. In this paper, the direct droplet-wall contact heat transfer mechanism is not included, so the cooling results could be probably 50% under predicted.…”
Section: Concerns and Future Researchmentioning
confidence: 99%
“…A promising technology is to enhance film cooling with mist (small water droplets) injection. Based on the aforementioned heat transfer mechanisms, mist can be used in gas turbine systems in different ways, including gas turbine inlet air fog cooling [10], overspray cooling through wet compression in the compressor [11], and airfoils (vanes and blades) internal cooling [12][13][14][15][16]. Recently, Li and Wang [17] conducted the first numerical simulations of air/mist film cooling.…”
Section: Introductionmentioning
confidence: 99%
“…The main objective of this thesis is to elucidate how the mass and dimension of the droplet affect the mist impingement cooling performance over a curved surface with a hole of double chamber model, calculated by CFD. Earlier studies discussed the mist film performance on the blade and combustor of gas turbine [10][11][12][13][14][15]. The model created in the paper looks like a flat with two double chambers, simulating the structure of transition piece.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the continuous evaporation of droplets can last farther into the downstream region where single-phase air film cooling becomes less effective. Based on the aforementioned heat transfer mechanisms, mist can be used in gas turbine systems in different ways, including gas turbine inlet air fog cooling [16], overspray cooling through wet compression in the compressor [17], and airfoils (vanes and blades) internal cooling [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%